PENGARUH PENGEMBANGAN KARIR DAN KOMPETENSI TERHADAP PRESTASI KERJA PEGAWAI - Nasution, Muhammad Irfan; Rahayu, Reni (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
The purpose of this study was to see the effect of career development, competence on employee work performance partially and simultaneously. The research method uses multiple linear regression analysis techniques. The results showed a significant effect of career development, competence on employee work performance partially and simultaneously.